The dark side of researching terrorism - Zul Kepli, Mohd Yazid; Malik, Maszlee; Mohd Yasin, Norhashimah (2018)
This article seeks to investigate the actual risks and challenges of researching terrorism, and attempts to classify the list of risks and challenges in a more systematic manner. This article is based on the content analysis of mutual evaluation reports, leading textbooks, and journal articles. It also benefited from the interviews with leading officers from the police force and the special unit on anti-terrorism, and academicians. The research methodology also includes analysis of previous leading literature, contemporary articles, newspaper articles and also interview with public on the issue of terrorism. While it is possible to reduce the risks and challenges, it is essential for any researcher of terrorism to be fully aware of them, so as to enable the researcher to make informed decision and take necessary precautionary measures to safeguard the researcher’s interest. This article reveals that conducting a research on terrorism can be sensitive, provocative, and dangerous. The article stresses the importance for researcher to be aware of the political climate, international and national laws and regulations and related legislations. The article concludes with a series of recommendations and suggestions for improvement.